Consumer Protection Law as an Extension of Civil Law Governance - Pelupessy, Sella Petrix (PT. Hafasy Dwi Nawasena, 2026)
The Civil Code, designed in a private relationship that is assumed to be balanced, often fails to provide effective protection for consumers as the economically and informationally weaker party. In this context, Law Number 8 of 1999 concerning Consumer Protection is present as a corrective instrument that extends the power of civil law governance, while simultaneously translating the constitutional mandate of Article 28D paragraph (1) of the 1945 Constitution into the realm of civil relations. This research uses a normative legal research method with a statute approach and a conceptual approach. Analysis is carried out on the provisions of the Consumer Protection Law, the Civil Code, and constitutional norms, by examining legal principles, the theory of lex specialis derogat legi generali, and the doctrine of legal interpretation that has developed in judicial practice. The purpose of this research is to examine the position of the Consumer Protection Law in the Indonesian civil law system, and to reconstruct the legal interpretation of the relationship between the Consumer Protection Law and the Civil Code so that consumer protection can function optimally without eliminating the general character of civil law. The research findings indicate that the Consumer Protection Act (UUPK) functions as a lex specialis, expanding and correcting general civil law by restricting freedom of contract, reversing the burden of proof, and strengthening the responsibilities of business actors. A systematic and teleological reconstruction of interpretation is necessary to address the ambiguity of norms and inconsistencies in law enforcement, so that civil law can achieve fair legal certainty and substantive protection for consumers